Perbandingan Luaran Klinis Pasien Stroke Hemoragik dengan Hipertensi dan Non Hipertensi di UPT RSUD Undata Provinsi Sulawesi Tengah Periode Maret 2020 – Maret 2022 - Suci Aulia; Fitriah Handayani; Ria Sulistiana; Gabriella Bamba Ratih Lintin (Yayasan Literasi Sains Indonesia, 2022)
Stroke is a neurological disorder characterized by blockage of blood vessels in the brain. This blockage will form a blood clot that can interfere with blood flow, clog arteries and end in rupture of blood vessels, which can cause bleeding and sudden death of brain cells due to lack of oxygen. To compare the clinical outcomes of hemorrhagic stroke patients with hypertension and non-hypertension at UPT RSUD Undata Central Sulawesi Province for the period March 2020-March 2022. This study used an observational analytic research method with a cross sectional design. The research sample was 44 people. The data collected is in the form of secondary data, namely medical records of hemorrhagic stroke patients who have hypertension and non-hypertension. The data obtained was then tested for normality using the Kolmogorov-Smirnov test, then processed using the Mann Whitney test and unpaired T test. The results of this study did not show a comparison of the clinical outcomes of hemorrhagic stroke patients with hypertension and non-hypertension. Barthel Index statistical test results before hospital admission (P 0.386) and Barthel Index statistical test results after hospital admission (P 0.336). There were no significant clinical outcome differences in hemorrhagic stroke patients with hypertension and non-hypertension at UPT RSUD Undata Central Sulawesi Province for the period March 2020-March 2022.